Preliminary Elucidation of the Mechanism Underlying Coal Degradation by Bacillus amyloliquefaciens - Chengyong Liu; Weilong Cao; Wenzhe Gu; Zhigang Wang; Yun Zhang; Fengtian Sheng; Beiyan Zhang; Chaofeng Yuan; Yaya Wang (BioResources, 2025)
China’s abundant low-rank coal faces challenges in utilization due to high moisture content and low calorific value. Microbial biodegradation has emerged as a promising method to improve coal quality. This study investigates the coal-degrading capabilities of the Bacillus amyloliquefaciens strain, designated as strain N7 in this study. Experimental results demonstrated that strain N7 significantly degraded lignite. On Luria-Bertani solid medium, the strain formed clear coal solubilization zones, indicating its biodegradation potential. Three-dimensional excitation-emission matrix fluorescence spectroscopy revealed humic-like substances, suggesting humic acid formation through oxidative depolymerization. Enzyme assays identified lignin peroxidase (LiP) and lipase as key contributors, with LiP showing particularly high activity. Scanning electron microscopy showed dense bacterial colonization on coal surfaces, implying efficient biodegradation through direct interaction. Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy indicated an increase in free hydroxyl groups in degraded coal, supporting structural breakdown. Degradation products analysis revealed 32% phenolic compounds and 55% long-chain alkanes, providing chemical evidence of lignite decomposition. These results highlight strain N7 as an effective microorganism for lignite biodegradation, offering insights for optimizing microbial coal bioconversion.